Endogenous Probes for Drug Transporters: Balancing Vision With Reality. Issue 3 (14th July 2017) - Rodrigues, AD; Taskar, KS; Kusuhara, H; Sugiyama, Y
Abstract : Various endogenous probes have been identified for a number of hepatic and renal drug transporters and available clinical data indicate that they could be leveraged in phase I trials to facilitate subject phenotyping and drug–drug interaction (DDI) assessment. Despite the progress, however, it is recognized that the menu of probes needs expanding, that existing probes need further characterization and validation, and that compound files need to be built in support of probe absorption‐metabolism‐distribution‐excretion‐DDI modeling exercises.